Implementation of Health Promotion through Education in Efforts to Prevent Non-Communicable Diseases at the Yosomulyo UPTD: Implementasi Promosi Kesehatan melalui Edukasi dalam Upaya Pencegahan Penyakit Tidak Menular di UPTD Yosomulyo - Rofana Aghniya; Prasetyowati Prasetyowati; Elisa Murti Puspitaningrum (Universitas Sumatera Barat, 2025)
Non-communicable diseases (NCDs) remain the leading causes of morbidity and mortality in Indonesia. One of the main contributing factors to this issue is the lack of public knowledge and awareness regarding risk factors and the importance of early prevention. This community service program aimed to improve knowledge and awareness among women of reproductive age about NCD prevention through health promotion and educational intejrventions. The activity was conducted at UPTD Yosomulyo Health Center on September 15, 2023, involving 60 participants. The methods included a pretest to assess baseline knowledge, interactive health education sessions using audiovisual materials and discussions, distribution of health promotion leaflets, and a posttest to evaluate knowledge improvement. The results showed a significant increase in participants’ understanding, where the proportion of respondents achieving high posttest scores (11–15) increased from 73% to 96%. This finding indicates that health promotion through structured educational interventions effectively enhances community knowledge and awareness regarding NCD prevention. The program demonstrates the importance of sustained health education initiatives as a promotive and preventive strategy, supporting national efforts to reduce the burden of NCDs through community empowerment and behavior change.